Effects of combination of melatonin and L-carnitine on in vitro maturation in mouse oocytes: An experimental study - Raziye Chegini; Morteza Sadeghi; Sadegh Shirian; Fatemeh Sabbaghziarani; Ehsan Aali; Pouriya Soleimani; Mohammad Reza Ashtari Majelan; Fariba Zafari; Shahram Darabi (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Melatonin and L-carnitine are free radical scavengers with antiapoptotic and antioxidant properties that improve oocyte development. Objective: This study aimed to find the possible effect of combining 2 antioxidant agents of melatonin and L-carnitine on oocyte morphology, maturation, apoptosis, and expression of bone morphogenetic protein 15 (BMP-15) and growth differentiation factor 9 (GDF-9) genes in a mice model. Materials and Methods: To overstimulation, 60 female NMRI mice were injected intraperitoneally using mare serum gonadotropin. On day 2 post-injection, 70 cumulus-oocyte complexes were collected from each mouse. The collected oocytes randomly were then divided into 4 groups including, the control, melatonin, L-carnitine, and melatonin + L-carnitine groups. The morphology and maturation rate of the oocytes was evaluated using a light microscope. Apoptosis was identified by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling assay and the expression of BMP-15 and growth and differentiation factor GDF-9 genes was also evaluated by real-time polymerase chain reaction. Results: Oocyte diameter significantly was increased in combination treatment of L-carnitine and melatonin compared to other groups (p < 0.05). L-carnitine group showed the highest mean percentage of oocyte cytoplasmic pattern. Results of the terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling indicated that the lowest apoptosis rate belonged to the melatonin + L-carnitine group. Moreover, the combination groups showed the highest number of oocytes and maturation rate. The BMP-15 and GDF-9 genes were significantly upregulated in all treatment groups compared to the control group. Conclusion: Our results suggested a combination of melatonin + L-carnitine administration as a more effective choice for in vitro promotion of oocyte maturation.